DFT and molecular docking study of Vladinol F as pF-DHFR-TS inhibitors - Muhammad Adrian Natsir; Engelbertus Dedycando Seran; Nikita Putri; Baso Ilham (Proceeding International Conference on Religion, Science and Education, 2023)
Molecular screening was a primer method used for drug discovery and to find the lead compounds. A high failure rate could be gotten when identifying some drug variables which did not meet the requirements so that it needed an alternative method development to resolve these deficiencies. In this research, NMR data correlation was used to encouraging the accuracy and precision when designing a potential compound; furthermore, molecular docking approach was used as the molecular screening to learn and inspect the drug mechanism to targeted enzyme. This research was conducted to study the potency of Vladinol F as antimalarial inhibitor. From the Mean Absolute Percentage Error (MAPE) data, it was obtained 8.80% and 12.23% for its proton and carbon respectively. Geometry structure and electronic properties was evaluated. Moreover, the observed activities, in vitro and in silico, were compared by docking study on P. falciparum dihydrofolate reductase-thymidylate synthase (pf-DHFR-TS).